2016
DOI: 10.1007/s12665-015-4971-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial trends of nitrate pollution and groundwater chemistry in Shimabara, Nagasaki, Japan

Abstract: 16Groundwater nitrate contamination in agricultural areas is a common problem in many parts of 17 the world. The important agricultural district Shimabara in Nagasaki, Japan, is also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 21 publications
2
41
0
Order By: Relevance
“…The application and results of the SOM support our previous conclusion (Nakagawa et al 2016) 326 regarding the spatial distribution of nitrate pollution in the study area and its causes. Data that display a 327 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 ...…”
Section: Summary and Conclusion 306supporting
confidence: 84%
See 1 more Smart Citation
“…The application and results of the SOM support our previous conclusion (Nakagawa et al 2016) 326 regarding the spatial distribution of nitrate pollution in the study area and its causes. Data that display a 327 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 ...…”
Section: Summary and Conclusion 306supporting
confidence: 84%
“…However, the Shimabara 53 groundwater has been increasingly polluted by nitrate since 1988. We analyzed the present situation of 54 groundwater pollution by nitrate in Shimabara and showed that agricultural activities are the main polluter 55 of the groundwater (Nakagawa et al 2016). To better understand characteristics of the water chemistry, 56 multivariate analysis such as principal component analysis (PCA), which can reduce data dimensionality 57 and extract synthetic indexes with minimum information loss, is often used (e.g., Aiuppa et al 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 1...…”
Section: Revised_manuscript_without_commentsmentioning
confidence: 99%
“…The correlation between nitrate and total dissolved solids may be related to geological factors, and it may also be related to the use of fertilizers. The positive correlation between nitrate and the total hardness may be related to the large-scale application of fertilizers in crop production [22], and it could also be related to geological factors. Positive correlation between nitrate and chloride may be related to the pollution effects of feces and livestock waste [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to intensive agricultural activities, the nitrate level in groundwater has increased to above the Japanese drinking water quality standard (10 mg L -1 ). According to Nakagawa et al (2016), 38% (15 out of 40 groundwater wells) exceed the permissible NO 3 -N + NO 2 -N concentration. The nitrate pollution in groundwater has been shown to be related to chemical fertilizer and livestock waste by use of the correlation matrix for major dissolved ion components.…”
Section: Introductionmentioning
confidence: 99%